PSYCHOLOGICAL COMPONENT OF HEALTH-SAVING COMPETENCE OF FUTURE TEACHERS: RESEARCH RESULTS - Melnyk, Inna (Educological discourse, 2021)
The article is devoted to the problems of psychological and pedagogical training. The urgency of the problem is due to lack of knowledge in society about effective mechanisms for maintaining, strengthening and restoring mental health in conditions of constant physical and intellectual overload, stress, social unrest, as evidenced by numerous facts of nervous breakdowns and psychosomatic diseases. The article highlights the quantitative and qualitative results of an empirical study of the psychological component of health competence in future teachers according to certain criteria - cognitive, motivational-value, activity and reflexive. The indicators of each of these criteria are described, as well as the used diagnostic tools for their study are described. It was found that the respondents do not have a high enough level of formation of the psychological component of health competence according to cognitive and reflexive criteria, which indicates the need for intensive work on the formation of deep knowledge of future teachers on the essence of "mental health" and ability to reflect in order to preserve and strengthen their own mental health and the health of children. Based on these results, the main ways and prospects for improving the level of formation of the psychological component of health competence of students on cognitive and reflexive criteria in the process of studying the course "Psychological Anthropology" were identified.